KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL (EQ) DI SMKN 1 GELUMBANG - Al Hafidh, Al Hafidh (UNISAN JURNAL, 2024)
The aim of this research is for school leadership based on emotional intelligence. This research uses a qualitative approach. Meanwhile, the method used in this research is a descriptive research method. The data collection techniques used were observation, interviews and documentation techniques. Based on the results of the description that has been described, SMKN 1 Gelumbang carries out primal leadership very well. This is proven based on triangulation of data and sources. Coconut school SMKN 1 Gelumbang has a high commitment to its vision for the future, especially during stressful times or in the midst of increasing responsibilities. Resonance of Coconut leadership at SMKN 1 Gelumbang as a form of leadership based on relatively good emotional intelligence. Anatomy-neurology Coconut school is able to read one’s own emotions and recognize their impact using instinct to guide decisions, knowing one’s strengths and limitations, being able to control emotions and showing honesty and integrity, worthiness to be trusted. Leadership domain Coconut school has good emotional control, shows honesty and integrity, adaptability, has the drive to improve performance to meet work standards, has initiative.